2011
DOI: 10.1177/1934578x1100600925
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Extract from Vitis vinifera Tendrils is Able to Enrich Keratinocyte Antioxidant Defences

Abstract: An aqueous extract of V. vinifera L. tendrils was evaluated for its ability to enrich the antioxidant capacity of cultured cells. The long-time antioxidant capability of the extract was measured by in vitro chemical methods, and its influence on reduced glutathione levels and plasma membrane oxido reductase activity was determined in cultured human keratinocytes (NCTC 2544). Keratinocytes are cells normally exposed to oxidative stress, and for this reason adequately equipped with antioxidant defences. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 39 publications
1
12
0
2
Order By: Relevance
“…The lack of toxicity was also supported by cell viability assessed using AB assay, with no sign of toxicity being observed in cells treated for 24 h with LE and TE at concentrations ranging from 10 to 400 µ g/mL (Figure 1). In agreement with the current results, which indicated a high cytocompatibility of the extracts, Fraternale et al reported that an aqueous extract from V. vinifera tendrils was not cytotoxic for human keratinocytes at a dose of up to 100 mg/mL [38]. Moreover, several other studies that evaluated the biological activities of aqueous or alcoholic extracts from different parts of V. vinifera indicated relatively low cytotoxicity on cultured cells, with the cancerous cell types displaying a higher sensitivity towards the cytotoxic effects of the extracts [41][42][43].…”
Section: Cytocompatibility and Cytoprotective Effect Of Le And Te Agasupporting
confidence: 93%
See 1 more Smart Citation
“…The lack of toxicity was also supported by cell viability assessed using AB assay, with no sign of toxicity being observed in cells treated for 24 h with LE and TE at concentrations ranging from 10 to 400 µ g/mL (Figure 1). In agreement with the current results, which indicated a high cytocompatibility of the extracts, Fraternale et al reported that an aqueous extract from V. vinifera tendrils was not cytotoxic for human keratinocytes at a dose of up to 100 mg/mL [38]. Moreover, several other studies that evaluated the biological activities of aqueous or alcoholic extracts from different parts of V. vinifera indicated relatively low cytotoxicity on cultured cells, with the cancerous cell types displaying a higher sensitivity towards the cytotoxic effects of the extracts [41][42][43].…”
Section: Cytocompatibility and Cytoprotective Effect Of Le And Te Agasupporting
confidence: 93%
“…Regarding grape tendrils, the data on the phenolic contents and the biological actions are very few or missing (derived from caffeic acids and antioxidant activity). Only Dawbaa et al (2017) and Fraternale et al (2011) obtained lower amounts of TPC and TFC [37,38].…”
Section: Total Phenolic Contents and Antioxidant Activitymentioning
confidence: 97%
“…The aqueous extracts of V. vinifera L. tendrils have the potential to enhance the antioxidant capacity of human keratinocytes (NCTC 2544). This effect is important as keratinocytes are often exposed to oxidative stress and need sufficient antioxidant defenses (Fraternale et al, 2011).…”
Section: Pharmacological Effectsmentioning
confidence: 99%
“…The total polyphenol content in the extract of tendrils was determined by the Prussian Blue method described by Hagerman and Butler [54], with slight modifications as reported by Fraternale et al [6].…”
Section: Polyphenol Contentmentioning
confidence: 99%
“…Extracts of various parts of Vitis vinifera L. have been reported to possess a broad spectrum of activities, including antioxidative, antiinflammatory, and antimicrobial [5]. Seeds, grape skin and leaves of V. vinifera have been reported to be rich in active polyphenols, such as flavonoids, catechins, epicatechins, procyanidins proanthocyanidins, resveratrol and other stilbene derivatives [6]. In the present study we investigated the ethanol extract of grape tendril (TVV) of V. vinifera (tendrils usually represent scrap material in the culture of V. vinifera) for its antifungal activity against plant pathogenic fungi such as, for example, Botrytis cinerea a wellknown pathogen of V. vinifera plants.…”
mentioning
confidence: 99%